Factors associated with acetabular degeneration and protrusion in bipolar hip hemiarthroplasty - Murat Bozkurt; Erkan Sabri Ertaş; Fahri Emre (Genel Tıp Dergisi)
Purpose This study aims to investigate the effect of some factors such as the diameter of bipolar prosthetic heads, body mass index (BMI), age, gender, bone mineral density (BMD) and leg length discrepancy (LLD) on the acetabular protrusion in elderly patients who had hip bipolar hemiarthroplasty (BHA) after femoral neck fractures. Methods The study included a total of 209 patients with a mean age of 77.4 ± 6.0 years who underwent BHA. The difference between the femoral head diameter of the patients and the diameter of the bipolar prosthetic head was divided into two groups, ranging from 0 to -2 mm (same and 1,2 mm small size) . Acetabular enlargement and cartilage degeneration were followed by standard AP pelvis radiographs and clinical outcomes were evaluated by the Harris Hip Score (HHS) after surgery and during 5 years of follow-up. Results During the 5-year follow-up, while HHS values decreased, acetabular diameter increased. Acetabular protrusion developed in 21 (10%) patients, acetabular revision surgery was performed for 36 (17%) patients, the difference between native femoral head diameter and prosthetic head diameter was significantly higher in these groups, as was mean LLD (p = 0.0001). Mean T scores obtained with BMD were lower in these groups (p = 0.0001). Conclusion It is safer and more reliable to use a bipolar prosthetic head the same size as the patient’s native femoral head in BHA. When considering the acetabular protrusion and revision surgery rate in this study, small-size bipolar prosthetic head implantation is not recommended and may cause devastating complications.